Adverse reactions after treatment with dasatinib in chronic myeloid leukemia: Characteristics, potential mechanisms, and clinical management strategies - Cheng, Fang; Xu, Qiling; Li, Qiang; Cui, Zheng; Li, Weiming; Zeng, Fang (Frontiers in Oncology, 2023)
Dasatinib, a second-generation tyrosine kinase inhibitor, is recommended as first-line treatment for patients newly diagnosed with chronic myeloid leukemia (CML) and second-line treatment for those who are resistant or intolerant to therapy with imatinib. Dasatinib is superior to imatinib in terms of clinical response; however, the potential pulmonary toxicities associated with dasatinib, such as pulmonary arterial hypertension and pleural effusion, may limit its clinical use. Appropriate management of dasatinib-related severe events is important for improving the quality of life and prognosis of patients with CML. This review summarizes current knowledge regarding the characteristics, potential mechanisms, and clinical management of adverse reactions occurring after treatment of CML with dasatinib.